Annual Report on the Working of State Electricity Boards & Electricity Departments February 1994 - Planning Commission (Planning Commission, 1994)
This report updates and reviews the working of the public sector power utilities in India, with particular reference to the State Electricity Boards (SEBs) and the Electricity Departments (EDs). Every year these agencies furnish detailed information to the Planning Commission in connection with the assessment of resources for the Annual Plans. The data used in this report are drawn mainly from the information furnished by these agencies for the Annual Plan 1994-95.
(Power & Energy Division) Planning Commission
(Power & Energy Division) Planning Commission